Relationship between cleft palate width and otitis media. Issue 6 (25th October 2022) - Yoshitomi, Ai; Baba, Shintaro; Tamada, Ikkei; Nakaya, Muneo; Itokawa, Masanari
Abstract: Objectives: To investigate the relationship between cleft width and otitis media (OM) and to determine whether a wide cleft palate (CP) is a risk factor of the incidence, type, amount of middle ear effusion, and prolonged morbidity in OM. Study Design: Retrospective cohort study. Methods: Children with CP who underwent palatoplasty between 2014 and 2018 were analyzed. Cleft width was measured at palatoplasty. The incidence of otitis media with effusion (OME) and acute otitis media (AOM), the type and amount of middle ear effusion, and OME duration and age at resolution were assessed in relation to cleft width. Results: One hundred eighteen children were included. The CP types were Veau I in 16, II in 35, III in 48, and IV in 19 patients. The incidence of OME and AOM before palatoplasty was 83.1% and 49.2%, respectively. Cleft width did not differ significantly between patients with or without OME but was significantly greater in those with, than in those without, AOM ( p < .001), in those with mucoid, than in those with serous, effusion ( p = .012), and in those with complete, than in those with partial, effusion ( p = .01). Regardless of cleft width or type, OME persisted for a median duration of 50 months. Conclusions: Cleft width was significantly associated with the incidence of AOM and the type and amount of middle ear effusion before palatoplasty. However, it was not significantly related to the incidence, age at resolution, or duration of OME. Regardless of cleft width or type, OM in children with CP requires long‐term follow‐up. Level of Evidence: 2b. Abstract : The relationship between cleft palate width and otitis media was investigated to determine whether a wide cleft palate is a risk factor of the incidence, type, amount of middle ear effusion and prolonged morbidity in otitis media. Cleft palate width was significantly associated with the incidence of acute otitis media and the type and amount of middle ear effusion before palatoplasty, but not with the incidence, age at resolution, or duration of otitis media with effusion (OME). Regardless of the width or type of cleft palate, OME persisted for a median of 50 months, and otitis media in children with cleft palate requires long‐term follow‐up.